2009
DOI: 10.1007/s10681-009-0017-2
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of beta-carotene-associated flesh color in cucumber (Cucumis sativus L.) fruit

Abstract: The nutritional value of cucumber (Cucumis sativus L.) can be improved by the introgression of b-carotene (i.e., provitamin A and/or orange flesh) genes from ''Xishuangbanna gourd'' (XIS; Cucumis sativus var. xishuangbannanesis Qi et Yuan) into US pickling cucumber. However, the genetics of b-carotene content has not been clearly defined in this US market type. Thus, three previous populations derived from a US pickling cucumber ('Addis') 9 XIS mating were evaluated for b-carotene content, from which the high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…Blast analysis results demonstrated that lycopene b-cyclase (Lcyb) mRNA, LCYB-red allele and complete cDNAs were detected in the same region between the two CAPS markers. In melon, seven genes from the carotenoid biosynthetic pathway have been previously mapped (Cuevas et al 2008(Cuevas et al , 2010, and five were re-mapped to similar locations with different markers, as reported by Harel-Beja and colleagues (Harel-Beja et al 2010). Identifying the gene and functional polymorphism underlying this position may further shed light on the carotenoid biosynthetic process.…”
Section: Caps Markers For Linkage Map Constructionmentioning
confidence: 73%
See 2 more Smart Citations
“…Blast analysis results demonstrated that lycopene b-cyclase (Lcyb) mRNA, LCYB-red allele and complete cDNAs were detected in the same region between the two CAPS markers. In melon, seven genes from the carotenoid biosynthetic pathway have been previously mapped (Cuevas et al 2008(Cuevas et al , 2010, and five were re-mapped to similar locations with different markers, as reported by Harel-Beja and colleagues (Harel-Beja et al 2010). Identifying the gene and functional polymorphism underlying this position may further shed light on the carotenoid biosynthetic process.…”
Section: Caps Markers For Linkage Map Constructionmentioning
confidence: 73%
“…QTL at chromosome 2 and 8 were associated with the presence and absence of flesh carotenoids, while the LSW-177 and COS F 2 population was established from a cross of red and pale yellow flesh color. Some studies showed that genetic manipulation of the quantity of b-carotene in cucumber and melon fruit (endocarp and mesocarp) was controlled by at least two recessive genes (Clayberg 1992;Cuevas et al 2010). It was suggested that the LG6 in melon QTL may contain a gene that stimulates the carotenoid metabolic pathway in general, leading to the formation of b-carotene (Monforte et al 2004;Cuevas et al 2008).…”
Section: Caps Markers For Linkage Map Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of genes that control exocarp color, which can also be orange, yellow, or cream-colored, have been described (Che and Zhang, 2019). Some cucumber varieties have colored flesh, such as yellow (Kooistra, 1971, Lu, H. W. et al , 2015) or orange (Simon and Navazio, 1997), due to carotenoid accumulation (Navazio and Simon, 2001, Cuevas et al , 2010), while the white flesh has no detectable ß-carotene and only trace amounts of total carotenoids (Kandlakunta et al , 2008). Carotenoids are yellow, orange, or red compounds with various functions in plants (Cazzonelli and Pogson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The flesh color of watermelon was controlled by two genes (Shimotsuma, 1963), but Gusmini and Wehner (2006) mentioned the genetic model of flesh color in the watermelon was affected by one gene or multiple genes that depended on the combinations of parents with different flesh colors. Cuevas et al (2010a) found the inheritance of beta-carotene content in the cucumber mesocarp was controlled by two recessive genes which affected the phenotype of flesh color, but inheritance of beta-carotene content in the endocarp was dominated by one recessive gene. The color appearances of the mesocarp and endocarp were independent.…”
Section: Introductionmentioning
confidence: 99%